A Graphene Oxide-Based Fluorescent Platform for Probing of Phosphatase Activity - Ting Sun; Ning Xia; Lin Liu (Nanomaterials, 2016)
We presented a strategy for fabricating graphene oxide (GO)-based fluorescent biosensors to monitor the change of phosphorylation state and detect phosphatase activity. By regulating the interaction between the negatively charged phosphate group and the positively charged amino residue, we found that GO showed different quenching efficiency toward the phosphorylated and dephosphorylated dye-labeled peptides. To demonstrate the application of our method, alkaline phosphatase (ALP) was tested as a model enzyme with phosphorylated fluorescein isothiocyanate (FITC)-labeled short peptide FITC–Gly–Gly–Gly–Tyr(PO32−)–Arg as the probe. When the negatively charged phosphate group in the Tyr residue was removed from the peptide substrate by enzymatic hydrolysis, the resulting FITC–Gly–Gly–Gly–Tyr–Arg was readily adsorbed onto the GO surface through electrostatic interaction. As a result, fluorescence quenching was observed. Furthermore, the method was applied for the screening of phosphatase inhibitors.